2018
DOI: 10.32539/jkk.v5i1.6122
|View full text |Cite
|
Sign up to set email alerts
|

Angka kejadian diabetes melitus pada pasien tuberkulosis

Abstract: Hubungan antara diabetes mellitus dan tuberkulosis dalam menyebabkan penyakit manusia telah dikenal selama berabad-abad. Intoleransi glukosa telah dilaporkan pada pasien TB aktif pengendalian hiperglikemia lebih sulit selama fase aktif tuberkulosis dan banyak pasien memerlukan insulin untuk mengendalikan hiperglikemia. Diabetes diperkirakan menjadi penyebab 15% kasus tuberkulosis saat ini, terutama karena diabetes merusak pertahanan host. Dalam penelitian ini dilakukan untuk mengetahui berapa besar angka kejad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
2
0
5
Order By: Relevance
“…The results of men aged >40 years old also became dominant in 2015 in Sebrang Ulu, Palembang 10 , while a study in India in 2018 reported that men aged >50 years old significantly increased the chances of morbidity of these two diseases. 11 These studies are relatable because older age is more vulnerable and the physiology of the patient's respiratory system is reduced, the barrier mechanism or microbial clearance can be damaged due to aging, 12 such as decreased ciliary function, pulmonary elasticity, and cough reflexes, which will increase the risk of infection with pulmonary TB 13 and added to T2DM disease can cause a decrease in cellular immune system, because blood sugar levels are always high and can reduce macrophage function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of men aged >40 years old also became dominant in 2015 in Sebrang Ulu, Palembang 10 , while a study in India in 2018 reported that men aged >50 years old significantly increased the chances of morbidity of these two diseases. 11 These studies are relatable because older age is more vulnerable and the physiology of the patient's respiratory system is reduced, the barrier mechanism or microbial clearance can be damaged due to aging, 12 such as decreased ciliary function, pulmonary elasticity, and cough reflexes, which will increase the risk of infection with pulmonary TB 13 and added to T2DM disease can cause a decrease in cellular immune system, because blood sugar levels are always high and can reduce macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…11 These studies are relatable because older age is more vulnerable and the physiology of the patient's respiratory system is reduced, the barrier mechanism or microbial clearance can be damaged due to aging, 12 such as decreased ciliary function, pulmonary elasticity, and cough reflexes, which will increase the risk of infection with pulmonary TB 13 and added to T2DM disease can cause a decrease in cellular immune system, because blood sugar levels are always high and can reduce macrophage function. 10 In this study, the diagnosis of a patient's pulmonary TB was classified according to the treatment history, between new cases of TB or TB with a previous history, to make it easier to see rifampicin resistance. Gene Xpert TB/RIF has been recommended by WHO since 2010 and later in 2013 expanded its use as an initial diagnostic test in all people with signs and symptoms of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Efek DM terhadap perkembangan dan kesembuhan TB diperantai oleh adanya peradangan yang disebabkan oleh sitokin Interleukin 6, dan Tumor necrosis factor α sebagai respon terhadap infeksi TB menyebabkan peningkatan resistensi insulin sehingga menimbulkan hiperglikemia pada pasien dan penurunan produksi insulin dengan efek samping penggunaan isoniazid dan rifampisin yang dapat menimbulkan hiperglikemik, hal tersebut tentu menyulitkan proses kesembuhan dan keberhasilan pengobatan pasien TB-DM (6). Faktor-faktor yang dapat berpengaruh terhadap keberhasilan pengobatan TB-DM antara lain jenis kelamin, usia, kepemilikan jaminan kesehatan (JKN), pekerjaan, dan riwayat pengobatan sebelumnya (12). Tingkat kesembuhan yang rendah pada pasien TB-DM dapat dipengaruhi oleh usia yang relatif tua, tidak menjadi peserta JKN, konsumsi alkohol, merokok, dan adanya penyakit lain (5).…”
Section: Aunclassified
“…Strategi pengobatan bagi pasien TB-DM perlu dilakukan secara agresif untuk mencapai kadar gula yang optimal. 11 Kegagalan pengobatan pasien TB-DM berhubungan dengan beberapa faktor antara lain terjadinya resistensi OAT, kepatuhan pengobatan, adanya lesi paru yang luas, adanya gangguan imunitas tubuh dan penurunan konsentrasi obat (terutama rifampisin) (12).…”
Section: Aunclassified
“…Gangguan neuropati saraf autonom berupa hipoventilasi sentral dan sleep apneu. Perubahan lain yang juga terjadi yaitu penurunan elastisitas rekoil paru, penurunan kapasitas difusi karbonmonok-sida, dan peningkatan endogen produksi karbondioksida (11) .…”
Section: Pembahasanunclassified